Leadership Approach of School Head and Educational Quality in Senior Secondary Schools in Ogun State - Rasheedat Modupe Oladimeji; Olawale Abayomi Onikoyi (Gagasan Pendidikan Indonesia, 2024)
According to the United Nations and international charters, education is a fundamental human right, it must be provided in the most effective possible way. However, stakeholders in the educational sector are deeply concerned about secondary schools' educational quality. Therefore, the study looks at the leadership approach of school head and educational quality in government senior secondary schools in Ogun state. For this study, a descriptive research design of the correlation type was used. 9,290 teachers from the 397 senior secondary schools spread across Ogun State. The study used a multistage sampling technique. A total of twenty five government senior secondary schools were chosen for the study. 278 teachers were chosen using Simple Random Sampling Technique. The Leadership Approach of School Head and Educational Quality Questionnaire (LASHEQQ) was to gather pertinent data from the participants. The instrument underwent reliability testing and validation. Data acquired for the study were statistically evaluated utilizing descriptive research statistic of frequency, percentage, mean rating and rank order to answer the research questions stated in the study. To test the theories, Pearson Product-Moment Correlation (PPMC) was employed. The study's conclusions showed that the leadership approach of school head have an impact on the educational quality of government senior secondary schools in Ogun state. Among other things, it was suggested that secondary school heads should not limit themselves to a single approach of leadership and that capacity building be conducted on a regular basis through seminars, workshops, and conferences to improve their leadership knowledge and skills.